Experimental investigations on finishing of a brass specimen by magneto-rheological honing technique. Issue 2 (November 2022) - Kumari, Chinu; Chak, Sanjay Kumar
Magneto-rheological abrasive honing (MRAH) is an unconventional surface finishing technique that relies on abrasives mixed with a unique finishing fluid, which changes its characteristics on magnetic field application. This process imparts nanometric-level surface finish with a significant amount of uniformity. Rotating motion of the workpiece and continuous reciprocation of the finishing fluid in the MRAH process are recognized as the major aspects for adopting this process in finishing non-magnetic materials. The finishing obtained through the MRAH process relies on the workpiece's material properties and process parameters such as concentration of abrasives in finishing fluid, rotational speed of the workpiece, and magnetic field strength/magnetizing current. To study the efficacy of MRAH process, a parametric study was conducted by performing few experiments on a brass workpiece. Design of experiment approach was adopted to plan the experiments, and the effect of different values of magnetizing current, the concentration of abrasives, and rotational speed on the surface finish were analyzed through the application of analysis of variance (ANOVA). From ANOVA, the rotational speed was found as the most significant parameter with a contribution of 48.90% on % reduction in roughness value (%∇Ra ). Around 57% of roughness reduction was obtained at the optimized value of process parameters.